2011
DOI: 10.1038/jp.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

The impact of feeding interval on feeding outcomes in very low birth-weight infants

Abstract: Objective: Test the hypothesis that very low birth-weight (VLBW) infants fed every 2 h (q2) are able to reach full enteral feedings more quickly than infants fed every 3 h (q3).Study Design: We performed a retrospective cohort study comparing q2 infants (n ¼ 103) with q3 infants (n ¼ 251). The primary outcome was days from start of a feeding advance to full feedings (120 ml per kg per day). Multivariable regression models were used to control for maternal and perinatal factors that preceded the initiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
1
19
1
3
Order By: Relevance
“…The results of this study were comparable with results from retrospective cohort studies by DeMauro et al ,13 a study including also extremely low birthweight (ELBW) infants, and by Rüdiger et al ,14 which included only ELBW infants.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study were comparable with results from retrospective cohort studies by DeMauro et al ,13 a study including also extremely low birthweight (ELBW) infants, and by Rüdiger et al ,14 which included only ELBW infants.…”
Section: Discussionsupporting
confidence: 89%
“…SB De Mauro and co-workers. 22,23 have done a study on the impact of feeding interval on feeding outcomes in very low birth-weight infants. They found that the preterm babies reach full feeding at 16 days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Several neonatology textbooks recommend a short interval for enteral feeding of lower‐birthweight infants . A recent study that compared feeding at intervals of 2 h and 3 h revealed some advantages of feeding every 2 h in very‐low‐birthweight (VLBW) infants . However, little is known about the effects of feeding interval on intestinal blood flow.…”
mentioning
confidence: 99%